Umbilical and ovarian endometriosis coexisting with multiple uterine myomas: A rare case report (Indian Journal of Case Reports, 2019)
Endometriosis and uterine fibroids are both independently associated with infertility/subfertility among women of reproductive age. Primary umbilical endometriosis is very rare and usually does not coexist with ovarian endometriomas. Endometriosis coexisting with uterine myomas has only been reported in few publications. Herein, we presented a patient with primary umbilical endometriosis with no previous history of surgery, with left ovarian endometriomas coexisting with multiple uterine fibroids. The diagnosis of umbilical endometriosis should be kept in mind while evaluating an umbilical mass. The ultrasound and magnetic resonance imaging features of endometriosis and uterine myomas have been presented. To the best of our knowledge, a similar case has not been reported before.